Effectiveness of statins on total cholesterol and cardiovascular disease and all-cause mortality in osteoarthritis and rheumatoid arthritis - Sheng, Xia; Murphy, Michael J; Macdonald, Thomas M; Wei, Li (Journal of rheumatology, 2012)
There is increasing prevalence of hypercholesterolemia among patients with osteoarthritis (OA) and rheumatoid arthritis (RA). We examined the effectiveness of statins on total cholesterol (TC), cardiovascular (CV) morbidity, and mortality in patients with OA or RA. A population-based cohort study was done using a record-linkage database in Tayside, Scotland. In total, 2024 OA or RA patients who had at least 2 separate TC measurements between 1993 and 2007 were studied. They were categorized into statin-exposed and statin-unexposed groups according to statin use status during followup. The main outcomes were TC concentration change from baseline, CV events, and all-cause mortality during the followup. Multivariate Cox regression models with a time-dependent variable for statins were employed to assess the risk of outcomes. Statin-associated TC concentrations in OA decreased by 15% in patients without CV disease (primary prevention, n = 1269) and 7% in patients with CV disease (secondary prevention, n = 247) from baseline of 5.30 mmol/l and 4.54 mmol/l, respectively. Correspondingly, in RA TC was reduced by 16% (n = 430) and 15% (n = 78) with baselines of 5.54 mmol/l and 4.95 mmol/l. In primary prevention, statins were associated with reduced CV events and all-cause mortality in RA patients [adjusted HR 0.45 (95% CI 0.20-0.98) and 0.43 (95% CI 0.20-0.92), respectively] and all-cause mortality in OA patients [adjusted HR 0.43 (95% CI 0.25-0.72)]. Statins were not associated with reduced risk of CV events or all-cause mortality in the secondary prevention of RA or OA patients [adjusted HR 0.68 (95% CI 0.30-1.54) and 0.52 (95% CI 0.20-1.34) for OA patients, and HR 0.58 (95% CI 0.07-4.79) and 0.79 (95% CI 0.18-3.53) for RA patients]. Statins reduced TC concentrations between 7% and 16% in patients with OA or RA. Statins were associated with reduced CV events and mortality in RA and mortality in OA in primary prevention.